Framework for impact: evaluating research methodology workshop using CIPP model - Sundar, Jasmine S.; E., Sivaranjani; S., Valarmathi; S., Kalpana; Narayanasamy, K.; G., Srinivas; Kumar, Raj; Paul, Arul; Punitha (International Journal of Research in Medical Sciences, 2025)
Background: Research is an integral part of medical education, yet medical students often lack sufficient research skills, hindering evidence-based medicine. Research methodology workshop aim to enhance these competencies, but their effectiveness requires systematic evaluation. This study assessed the impact of an online research methodology and biostatistics workshop for final year undergraduate medical students using the content, input, process and product (CIPP) evaluation model. Methods: A quasi-experimental study was conducted among 2,982 final-year Part-I undergraduate medical students from colleges affiliated with The Tamil Nadu Dr. M. G. R Medical University. The intervention involved periodic online workshops with interactive sessions led by expert facilitators. A 15-item semi-structured questionnaire was administered pre- and post-workshop to assess knowledge. The CIPP model guided evaluation. Results: A significant improvement in research knowledge was observed following the workshop. The mean pre-test score increased from 7.67±3.22 to 9.37±2.20 post-test. The proportion of students scoring above the mean increased from 34.6% to 54.2%. Participants reported increased confidence in identifying study designs, formulating research questions, and interpreting statistical data. Qualitative feedback highlighted the workshop’s relevance, engagement, and value in fostering a research-oriented mindset. Conclusions: The online workshop effectively enhanced research knowledge and competencies among medical students. Using the CIPP model, demonstrated the workshop’s role in fostering evidence-based practice and research culture. Early exposure to research methodology is vital for developing clinicians capable of contributing to medical advancements. Future studies should explore the long-term impact on research engagement and clinical practice.